1965
DOI: 10.4319/lo.1965.10.3.0434
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Marine Protozoa on Nutrient Regeneration1

Abstract: Per unit weight, marine protozoa excrete dissolved phosphorus one to two orders of magnitude faster than marine microcrustaceans and several orders of magnitude faster than marine macrofauna.Protozoa may therefore be responsible for a major fraction of faunal nutrient excretion even though present only as a minor fraction of the faunal biomass.Regeneration of dissolved inorganic phosphate from organic detritus proceeds faster and more completely in the presence of bacteria and ciliates or colorless flagellates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
111
0
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(118 citation statements)
references
References 13 publications
6
111
0
1
Order By: Relevance
“…Our estimates of BEET (QPI Ep-') for Paraphysomonas imperforafa ranged from 0.6 to 2 d (Table 4), values which are considerably longer than the tens of minutes found by Johannes (1965) for several Protozoa excreting phosphorus. Taylor & Lean (1981) similarly found that phosphorus turnover times for a ciliate and a rotifer were on the order of tens of hours.…”
Section: Role Of Microflagellates In Nutrient Regenerationmentioning
confidence: 60%
See 3 more Smart Citations
“…Our estimates of BEET (QPI Ep-') for Paraphysomonas imperforafa ranged from 0.6 to 2 d (Table 4), values which are considerably longer than the tens of minutes found by Johannes (1965) for several Protozoa excreting phosphorus. Taylor & Lean (1981) similarly found that phosphorus turnover times for a ciliate and a rotifer were on the order of tens of hours.…”
Section: Role Of Microflagellates In Nutrient Regenerationmentioning
confidence: 60%
“…Taylor & Lean (1981) similarly found that phosphorus turnover times for a ciliate and a rotifer were on the order of tens of hours. These authors criticized the conclusion of Johannes (1965) that Protozoa regenerate a larger proportion of their ingested nutrients than do Metazoa. They pointed out that, even though Protozoa have greater weight-specific metabolic rates than do Metazoa, they also have extremely high gross growth efficiencies: in effect, Protozoa retain a large fraction of the nutrients they incorporate.…”
Section: Role Of Microflagellates In Nutrient Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Johannes (1965) demonstrated that remineralization 1a enhanced by the presence of both bacteria and protozoa, compared to just bacteria alone. Evidence aa to the importance of these microorganisms in organic matter cycling is steadily sccumulating (e.g .…”
Section: List Of Tables (Continued)mentioning
confidence: 99%